PRAGMATISM IN PHILOSOPHY OF INCLUSIVE EDUCATION STUDIES AND PROBLEMS OF TEACHER TRAINING - Vasianovych, Hryhorii; Budnyk, Olena; Klepar Mariіa; Beshok, Tetiana; Blyznyuk, Tetyana; Latyshevska, Kateryna (Revista Inclusiones, 2021)
The article analyzes the essence and content of philosophical, psychological and pedagogical aspects of classical pragmatism and neopragmatism. The studies of texts by American scholars Charles Sanders Peirce, William James, John Dewey have proved that the founders of pragmatism set out to substantiate a scientific method that would actively contribute to the versatile knowledge of human beings as well as their physical, psychological, social, mental and moral abilities. Charles Pierce, basing this method on two main principles: 1) a principle of doubt and belief and 2) a principle of meaning, argued that a person, who remains in constant unrest and uneasiness should get rid of these “persecutors”, overcome doubt and move on to a mental balance, peace of mind and happiness. Undoubtedly, this idea has relevance for children with special needs who, being acutely affected by their condition, sometimes fell into despair due to insufficient opportunities for self-realization. The way out of these states can, in the opinion of representatives of pragmatism, be found with the help of life experience, which is acquired by intellectual activities.